Effect of selenium on ''low T3 syndrome '' in hepatic failure - Dönder, Emir; Çay, Mehmet; İlhan, Necip; Baydaş, Gıyasettin; Nazıroğlu, Mustafa (My University, 1998)
Triiodothyronine occurs especially in S'-monodeiodination of thyroxin in peripheral tissues. Deiodination of thyroxin mainly occurs in the liver. The enzyme which catalyzes this reaction is a seleno-enzyme. Deiodinase enzyme activity and the triiodothyronine level decrease in selenium deficiency. After the occurrence of chronic hepatic failure by carbon tetrachloride in rats, we gave sodium selenite to these rats. Then, we tried to evaluate the changes in thyroid hormone levels. Liver function tests, thyroxin and triiodothyronine levels, and hepatic 5'-deiodinase and glutathione peroxidase enzyme activities were measured. Triiodothyronine levels in the carbon tetrachloride group and carbon tetrachloride + selenium group were significantly lower than in the control group (P<0.01, P<0.05, respectively). In the carbon tetrachloride + selenium group, the level of triiodothyronine was higher than in the carbon tetrachloride group (P<0.05). Deiodination of thyroxin was impaired in hepatic failure. Selenium couldn't prevent the inhibition of hepatic deiodination of thyroxin completely.
Keywords: Endokrinoloji ve Metabolizma; Genel ve Dahili Tıp